Muang rae geothermal system: Drilling and borehole geophysics, 1000-m core hole into granitic rock, amphoe pai, mae hong son province, northern Thailand - Wood S. (2017)
In 2015, a 1-km core hole was drilled into granitic rock at the Muang Rae geothermal area. Previous drilling in 1993 to 200 m was unsuccessful in obtaining flows, but one of the "dry" wells began flowing in August, 2013 at 9.75 L/s of 96.9°C water from a fracture zone 80 m deep. In the sandy bed of the Pai River, 150 m south of that well is a 600-m long line of hot seeps, oriented NE, with highest temperature measured at 94.5°C. Geology is foliated Triassic () granitic rock cut by a NE-SW-trending normal fault zone (dip 65° NW) with extensive fluorite mineralization. Mineral equilibrium geothermometer analysis predicts a reservoir temperature of 132°C. The core hole was sited NW of the seep zone to drill into the fault zone at 600 m. MT indicated a low-resistivity anomaly 150-500 m deep at the site. The well did not flow, but was pumped at 6.4 L/s of 86°C water with 2.5 m of drawdown. Temperature logs indicate the well intersects a fracture with flowing hot water of 91.5°C at 600 m. The log shows a temperature inversion related to the transient effect of conductive heating of the surrounding rock by hot-water flow in the fracture. The bottom 150 m of the well shows a 23°C/km temperature gradient, which reflects the regional crustal conductive gradient.